Risky sexual practices and associated factors among taxi drivers in the Finoteselam town, northwest Ethiopia, 2023: a community-based cross-sectional study - Laikemariam, Melaku; Fetene, Yetwale (Frontiers in Reproductive Health, 2024)
BackgroundRisky sexual practices among taxi drivers pose a significant threat to public health, contributing to the spread of sexually transmitted infections (STIs) and HIV/AIDS. The nature of their profession often exposes taxi drivers to factors that increase their vulnerability to engaging in risky sexual practices. Although research on sexual health in general is readily available, studies specifically focused on this population are limited. Understanding the contributing factors behind risky sexual practices among taxi drivers is crucial to developing targeted interventions that address their unique needs and vulnerabilities.ObjectivesTo assess the prevalence and associated factors of risky sexual practices among taxi drivers in Finoteselam town, northwest Ethiopia, 2023.MethodsA cross-sectional study was conducted among 359 taxi drivers in the Finoteselam town. Data were collected using pre-tested questionnaires and analyzed using SPSS. Bivariate and multivariable analyses were performed to identify factors associated with risky sexual practices. In the bivariate analysis, a p-value ≤ 0.25 at 95% CI was used to consider the variables in the multivariate analysis. Finally, statistical significance was declared with a p-value of less than 0.05 with a 95% CI.ResultsThe prevalence of risky sexual practices among taxi drivers was 32.9 (95% CI: 28.01, 38.7). Living alone (AOR = 3.47, 95% CI: 1.86, 6.48), taxi ownership (AOR = 2.08, 95% CI: 1.01, 4.25), neglecting the discussion of the SRH issue (AOR = 2.05, 95% CI: 1.08, 4.00), substance use (AOR = 1.56, 95% CI: 1.04, 2.09), attending night clubs (AOR = 6.04, 95% CI: 1.97, 18.55) and watching pornographic materials (AOR = 4.44, 95% CI: 2.14, 9.19) were significantly associated with risky sexual practices.Conclusions and recommendationThis study revealed a high prevalence of risky sexual practices among taxi drivers in Finoteselam town. Therefore, a comprehensive approach involving different stakeholders is required for reducing risky sexual practices. Information dissemination, awareness creation (about risks of attending nightclubs, substance use, and watching pornography), and encouraging knowledge sharing about sexual health are some of the interventions required to reduce risky sexual practices among taxi drivers.